2018
DOI: 10.14260/jemds/2018/298
|View full text |Cite
|
Sign up to set email alerts
|

Priming Principle and Rapid Sequence Intubation With Non-Depolarising Muscle Relaxant Vecuronium Bromide

Abstract: BACKGROUND Succinylcholine cannot be used for rapid sequence intubation (RSI) in several situations due to associated side effects. Vecuronium bromide has faster onset of time among non-depolarising muscle relaxants and can offer safe alternative for RSI when the priming principle used. The aim of the study is to evaluate the intubating conditions and time required for rapid, smooth tracheal intubation using the "principle of priming" with non-depolarising muscle relaxant vecuronium bromide. The objective of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Adequate intubating conditions were achieved in 63 seconds in all patients. 19 So, it can be seen that our observations are consistent with observations of Schmidt J et al, Duggappa et al, Veena et al and Rao MS et al That priming significantly reduces the onset time of NDMR and also this reduction is higher with higher priming doses.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Adequate intubating conditions were achieved in 63 seconds in all patients. 19 So, it can be seen that our observations are consistent with observations of Schmidt J et al, Duggappa et al, Veena et al and Rao MS et al That priming significantly reduces the onset time of NDMR and also this reduction is higher with higher priming doses.…”
Section: Discussionsupporting
confidence: 93%
“…In their study Rao MS et al found that intubating conditions were clinically acceptable in all three groups where two different priming doses were used in two groups and no priming was used in a group. 19 Study done by Sindhu K. Sridhar et al showed that intubating conditions were clinically acceptable in all three groups. Intubating conditions were compared by the Cooper scoring system.…”
Section: Discussionmentioning
confidence: 91%